Esthesiometric evaluation of corneal analgesia after topical application of 1% morphine sulfate in normal horses. (17th July 2017) - Gordon, Emma; Sandquist, Christy; Cebra, Christopher K.; Heidel, Jerry; Poulsen, Keith; Schlipf, John W.
Abstract: Objective: To evaluate whether topical ocular application of 1% morphine sulfate would change corneal sensitivity and to identify the duration of action. Animal studied: Eight healthy adult horses. Procedure: Corneal touch threshold (CTT) was measured in the center of one randomly selected eye of each horse by Cochet–Bonnet esthesiometer (Luneau Cochet–Bonnet Esthesiometer; Western Ophthalmics, Lynnwood, WA, USA). Immediately following baseline CTT measurement, 0.3 ml of 1.0% preservative‐free morphine sulfate (Morphine Sulfate 25 mg/ml Preservative‐free; Hospira, Lake Forest, IL, USA) (3 mg) was applied to the tested eye. The same volume of artificial tear (LiquiTears; Major Pharmacauticals, Livonia, MI, USA) solution was then applied to the control eye following acquisition of baseline CTT. Corneal touch threshold was then subsequently measured at 1 min after medication application, followed by every 5 min until 60 min post administration. If the corneal touch threshold had not returned to baseline by 60 min, measurements were continued at 15‐min intervals until corneal sensitivity returned to baseline CTT measurement up to 180 min post administration if needed. The control eye was treated identically and measurements on the control eye stopped when the corresponding treated eye returned to baseline. Results: Mean baseline CTT of both eyes was 21.8 mm with an identical range of 15–30 mm. Mean corneal touch threshold was not statistically different between morphine‐treated and control eyes ( P = 0.22). There was a large degree of inter‐ and intrasubject variation in the CTT measurements obtained. All but three horses were considered to be at baseline values by 60 min. Conclusions: Topical ophthalmic 1% morphine sulfate did not have a clinically significant analgesic effect on the corneal touch threshold of intact healthy equine corneas.